Efficacy comparison of oral rehydration solutions containing either 90 or 75 millimoles of sodium per liter - Pizarro Torres, Daniel (1987)
In a randomized trial, 62 infants 2 to 35 months of age with dehydration due to acute watery diarrhea were allocated to one of two groups: group A received solution A (World Health Organization-recommended oral rehydration solution), which contained (mmol/L): Na+ 90, K+ 20, Cl- 80, citrate3- 10, and glucose 110; group B received solution B (Pedialyte RS; Abbott Laboratories, North Chicago), which contained (in mmol/L): Na+ 75, K+ 20, Cl- 65, citrate3- 10, and glucose 139. Oral therapy was given until clinical signs of hydration status were normal. During the 48-hour trial, the following laboratory data were collected: blood gases, serum electrolytes, glucose, urea, and creatinine values and sodium and potassium concentrations in stool and urine; serial weights and clinical signs were also reported. Six of the 62 infants, three in each group, required intravenous fluids because of high stool output. Results of clinical outcome and normalization of altered serum electrolyte values were similar in both groups. During the 48-hour trial, eight patients in group A and four in group B had mild, asymptomatic hypernatremia. Pedialyte RS was found to be a safe glucose/electrolyte solution for oral rehydration therapy.